Self-nanomicellizing solid dispersion of edaravone: part II: in vivo assessment of efficacy against behavior deficits and safety in Alzheimer’s disease model - Parikh A; Kathawala K; Li JT; Chen C; Shan Z; Cao X; Wang YJ; Garg S; Zhou XF (Dove Medical Press, 2018)
Ankit Parikh,1 Krishna Kathawala,1 Jintao Li,1,2 Chi Chen,1,3 Zhengnan Shan,1 Xia Cao,3 Yan-Jiang Wang,4 Sanjay Garg,1 Xin-Fu Zhou1 1School of Pharmacy and Medical Sciences, University of South Australia, Adelaide, SA, Australia; 2Neuroscience Institute, Kunming Medical University, Kunming, Yunnan, China; 3Central Laboratory, Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, China; 4Department of Neurology, Daping Hospital, Third Military Medical University, Chongqing, Sichuan, China Background: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder that lacks any disease-modifying drug for the prevention and treatment. Edaravone (EDR), an approved free radical scavenger, has proven to have potential against AD by targeting multiple key pathologies including amyloid-beta (Aβ), tau phosphorylation, oxidative stress, and neuroinflammation. To enable its oral use, novel edaravone formulation (NEF) was previously developed. The aim of the present investigation was to evaluate safety and efficacy of NEF by using in vitro/in vivo disease model. Materials and methods: In vitro therapeutic potential of NEF over EDR was studied against the cytotoxicity induced by copper metal ion, H2O2 and Aβ42 oligomer, and cellular uptake on SH-SY5Y695 amyloid-β precursor protein (APP) human neuroblastoma cell line. For in vivo safety and efficacy assessment, totally seven groups of APP/PS1 (five treatment groups, one each as a basal and sham control) and one group of C57BL/6 mice as a positive control for behavior tests were used. Three groups were orally treated for 3 months with NEF at an equivalent dose of EDR 46, 138, and 414 μmol/kg, whereas one group was supplied with each Donepezil (5.27 μM/kg) and Soluplus (amount present in NEF of 414 μmol/kg dose of EDR). Behavior tests were conducted to assess motor function (open-field), anxiety-related behavior (open-field), and cognitive function (novel objective recognition test, Y-maze, and Morris water maze). For the safety assessment, general behavior, adverse effects, and mortality were recorded during the treatment period. Moreover, biochemical, hematological, and morphological parameters were determined. Results: Compared to EDR, NEF showed superior cellular uptake and neuroprotective effect in SH-SY5Y695 APP cell line. Furthermore, it showed nontoxicity of NEF up to 414 μM/kg dose of EDR and its potential to reverse AD-like behavior deficits of APP/PS1 mice in a dose-dependent manner. Conclusion: Our results indicate that oral delivery of NEF holds a promise as a safe and effective therapeutic agent for AD. Keywords: edaravone, Soluplus, dose–response relationship, APPSwe/PS1deE9 mice, learning and memory, safety assessment